Concession is a Determinant for The Implementation of Telecommunication Technology Field in Indonesia (Journal of Governance and Development (JGD), 2018)
The existence of concessions in Indonesia is actually not a new thing, because previously it was regulated during the Dutch colonial era, which was stated in Burgilijk Wetboek (BW), under the 1899 Indische Mijnwet law which stipulates that all mining cooperation is granted in the form of concessions to Dutch citizens and their allies to explore and exploit the wealth of Mining Resources in Indonesia. And in its development, the concession in Law Number 30 of 2014 concerning Government Administration in Article 1 number 20 is given a deï¬nition as: a decision of the Governmental Ofï¬cer authorized as a form of agreement from the approbation of government bodies and/ or ofï¬cials with other government bodies and/ or ofï¬cials in the management of public facilities and/ or natural resources and other management in accordance with the provisions of the legislation. However, at reality the concession in Indonesia is only limited to be used as an approbation or agreement in terms of natural resource management and transportation only, while in terms of the implementation of services related to the public interest, the concession has not been fully utilized. Just like what the author did to do research with the theme of concessions in the ï¬eld of telecommunication technology. The ï¬rst purpose of the objective paper is present that concessions license could be applied to telecommunication technology ï¬elds in Indonesia and the second is to provide all the regulation in Indonesia that is needed for regulate concessions license for the telecommunication technology ï¬eld in Indonesia. In conducting this research the author uses the analysis contents method of the regulations that related with concession license, where is the regulation is provided by the National Law Ofï¬ce in the under of Indonesian Ministry of Law and Human Rights as a provider of data banks for all the regulations that exist in Indonesia. And in addition, besides using the content analysis method of the regulations, the author is also use literature research method from several journals as supporting data. This study does not rule out the possibility that concessions can help and be used in many other ï¬elds that are closely related to the public interest that need to be served by the Government of Indonesia. This paper contributes a mind framework for policy makers and government to use concession license for improving the public interest service.